2015
DOI: 10.1111/gfl.12160
|View full text |Cite
|
Sign up to set email alerts
|

Fluid mapping in deeply buried Ordovician paleokarst reservoirs in the Tarim Basin, western China

Abstract: The storage spaces within deeply buried Ordovician paleokarst reservoirs in the Tarim Basin are mostly secondary and characterized by strong heterogeneity and some degree of anisotropy. The types of fluids that fill the spaces within these reservoirs are of great importance for hydrocarbon exploration and exploitation. However, fluid identification from seismic data is often controversial in this area because the seismic velocity for this particular reservoir could be significantly influenced by many factors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…The multi-period fractures formed by faults and unconformities are mutually cut, combined with a variety of dissolved pores, resulting in extremely strong heterogeneity [41][42][43][44][45]. The paleokarst reservoirs are the main storage space and have experienced multiple stages of tectonic movements and longtime diagenetic processes [46][47][48]. The main karstifications were in the late Caledonian and Early Hercynian, and the karst system was buried and was not reactivated as a result of epeirogenetic movements and erosion of the overburden.…”
Section: Methodsmentioning
confidence: 99%
“…The multi-period fractures formed by faults and unconformities are mutually cut, combined with a variety of dissolved pores, resulting in extremely strong heterogeneity [41][42][43][44][45]. The paleokarst reservoirs are the main storage space and have experienced multiple stages of tectonic movements and longtime diagenetic processes [46][47][48]. The main karstifications were in the late Caledonian and Early Hercynian, and the karst system was buried and was not reactivated as a result of epeirogenetic movements and erosion of the overburden.…”
Section: Methodsmentioning
confidence: 99%
“…Because the velocity of P-wave decreases obviously after passing through the gas-bearing reservoir, but the velocity of Swave does not change obviously, so the velocities of P-wave and S-wave are the key parameters for reservoir and fluid identification and prediction, and the velocity of S-wave plays an important role in petrophysical analysis and AVO forward modeling [22][23][24]. The quality of S-wave curve is difficult to control, so it is necessary to effectively predict Swave velocity through petrophysical experiment and logging curve intersection analysis [25].…”
Section: Estimation Of S-wave Velocity Using P-wave Velocitymentioning
confidence: 99%
“…Pre-stack inversion has rarely been applied to the Tarim Basin. A previous researcher [14] physically modeled the seismic response of a karst cave, and drew some conclusions surrounding the effects of the cave scale, velocity, spatial distribution, shape, and fluids on the "beads" and the corresponding relationships between six types of "beads" and karst caves; However, there is no validity analysis for pre-stack inversion. The authors of [15][16][17][18][19] used pre-stack inversion based on seismic data for an Ordovician TZ45 area, and indicated that pre-stack inversion can be applied for cave carbonate reservoir prediction.…”
Section: Introductionmentioning
confidence: 99%